2017
DOI: 10.1128/aac.02466-16
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Trough Total and Unbound Teicoplanin Concentrations and Achievement of Therapeutic Drug Monitoring Targets in Adult Patients with Hematological Malignancy

Abstract: The objective of this study was to explore the following aspects of teicoplanin use in patients with hematological malignancy: early attainment of target trough concentrations with current high-dose teicoplanin regimens, variability in unbound teicoplanin fractions, factors associated with observed total and unbound trough concentrations, efficacy and toxicity, and renal function estimation. This was a single-center, prospective study. Samples for determination of trough concentrations were taken on days 3, 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…This is consistent with previous research. 9 , 14 , 15 , 17 , 20 , 21 , 23 , 27 , 29 All patients were divided into groups based on Cl cr and loading regimens. As a result, ratios of the 3-day loading dose to Cl cr and C min were significantly correlated ( R =0.59, P <0.001; Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research. 9 , 14 , 15 , 17 , 20 , 21 , 23 , 27 , 29 All patients were divided into groups based on Cl cr and loading regimens. As a result, ratios of the 3-day loading dose to Cl cr and C min were significantly correlated ( R =0.59, P <0.001; Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a PK study of healthy volunteers, multiple-dose teicoplanin administration from 3 to 12 mg/kg of body weight showed a linear dose-serum concentration relationship [21]. However, the dose-serum concentration in critically ill patients can be highly variable [22][23][24]. Serum albumin concentrations are an important determinant of PK for antibiotics that have a high binding affinity to albumin such as teicoplanin.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetics of teicoplanin has been steadily studied in various clinical settings, including adult patients, 5 10 11 12 13 pediatric patients, 14 15 16 17 18 19 20 and patients with hematologic malignancies. 21 22 23 24 25 A number of studies on the pharmacokinetics of teicoplanin have shown a common problem that the therapeutic range of trough level is not achieved early and occasionally not reached even at steady state. To overcome this problem, the need of loading dose has been suggested.…”
Section: Discussionmentioning
confidence: 99%